A Strength-Based Assessment for Optimizing Local Potential: A Study of Lingga Village, Muara Enim Regency, Indonesia - Nastia, Gina Indah Permata; Pratama, Yudhistira Anugerah (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2023)
This study highlights the compelling need for a strength-based assessment model in Corporate Social Responsibility (CSR) initiatives, with a specific focus on Lingga Village. The data identify four integral forms of capital–physical, human, financial, and social–signifying the diverse potential within the community for sustainable development. This research was conducted using a qualitative descriptive analysis method with a total of 619 respondents. The results indicate that Lingga Village has a number of potential strengths and boasts robust Physical Capital, evident in its educational, health, religious, and sports facilities, providing a solid groundwork for a strength-based CSR approach. The concentration in elementary schools offers opportunities for targeted educational initiatives. Human Capital is characterized by a productive population engaged in diverse livelihoods, providing a foundation for skill-building programs and livelihood support. Financial Capital, manifested through asset ownership and participation in assistance programmes, underscores the importance of supporting and expanding existing businesses, enhancing financial literacy and exploring economic empowerment opportunities. Social Capital, reflected in family resilience and community cohesion, highlights the community's strong social network, emphasizing the need for collaborative problem solving and reinforcing familial bonds. Moreover, Lingga Village exhibits rich religious and cultural capital that can be leveraged to support activities that enhance religious knowledge, cultural practices, and community cohesion. A strength-based CSR approach, encompassing education, skills development, economic empowerment, and cultural preservation, holds the potential to empower the Lingga Village community. This model aligns with the principles of social work, emphasizing empowerment, collaboration, positive change in community dynamics, and encouraging long-term sustainability and resilience. Keywords: Corporate Social Responsibility, Strength-based assessment, Lingga Village, Physical human financial and social capital, Sustainable development   Studi ini menyoroti kebutuhan mendesak akan model penilaian berbasis kekuatan untuk inisiatif Tanggung Jawab Sosial Perusahaan (CSR), dengan fokus khusus pada Desa Lingga. Data yang diperoleh mengidentifikasi empat bentuk modal yang tidak terpisahkan-fisik, manusia, keuangan, dan sosial, yang menandakan beragamnya potensi masyarakat untuk pembangunan berkelanjutan. Penelitian ini dilakukan dengan menggunakan metode analisis deskriptif kualitatif dengan jumlah responden sebanyak 619 orang. Hasil penelitian menunjukkan bahwa Desa Lingga memiliki sejumlah potensi kekuatan dan memiliki modal fisik yang kuat, terlihat dari fasilitas pendidikan, kesehatan, keagamaan, dan olahraga, yang memberikan dasar yang kuat untuk pendekatan CSR berbasis kekuatan. Konsentrasi pada sekolah dasar menawarkan peluang untuk inisiatif pendidikan yang ditargetkan. Sumber Daya Manusia dicirikan oleh populasi produktif yang terlibat dalam berbagai mata pencaharian, memberikan landasan bagi program-program pengembangan keterampilan dan dukungan mata pencaharian. Modal Finansial, yang diwujudkan melalui kepemilikan aset dan partisipasi dalam program bantuan, menggarisbawahi pentingnya mendukung dan mengembangkan bisnis yang sudah ada, meningkatkan literasi keuangan dan menjajaki peluang pemberdayaan ekonomi. Modal Sosial, yang tercermin dalam ketahanan keluarga dan kohesi masyarakat, menyoroti jaringan sosial masyarakat yang kuat, menekankan perlunya pemecahan masalah secara kolaboratif dan memperkuat ikatan kekeluargaan. Selain itu, Desa Lingga memiliki modal agama dan budaya yang kaya yang dapat dimanfaatkan untuk mendukung kegiatan yang meningkatkan pengetahuan agama, praktik budaya, dan kohesi masyarakat. Pendekatan CSR berbasis kekuatan, yang mencakup pendidikan, pengembangan keterampilan, pemberdayaan ekonomi, dan pelestarian budaya, memiliki potensi untuk memberdayakan masyarakat Desa Lingga. Model ini selaras dengan prinsip-prinsip pekerjaan sosial, yaitu menekankan pada pemberdayaan, kolaborasi, dan perubahan positif dalam dinamika masyarakat serta mendorong keberlanjutan dan ketahanan jangka panjang. Kata kunci: Tanggung Jawab Sosial Perusahaan, Assesmen berbasis kekuatan, Desa Lingga, Modal Fisik manusia finansial dan sosial, Pembangunan berkelanjutan